The Environmental Issues Relating to Packaging in the UK Food Sector - Jiang, Bo (2007)
This dissertation's objective is to explore a practical and cost-effective way to alleviate the environmental burden coming from food and food packaging industries, to establish a win-win solution between the call for environmental-friendly packaging and the producers' actual cost. To achieve this aim, the author implemented both primary and secondary research methods, and has recorded her findings according to these two kinds of researches in Chapter 4. Combining the findings with her academic background, the author gives her recommendations from industry logistics and supply chain perspectives.